MEMBANGUN KAMPUS ( STAIN PEKALONGAN) YANG SENSITIF GENDER - Triana Sofiani (UIN K.H. Abdurrahman Wahid Pekalongan, 2012)
Abstract : This study moved from the reality of the problems that have been the subject of conversation in forums network PSG / PSW throughout Indonesia, both PTAIN/S and Public Higher Education, regarding the condition of lack of response to campus officials agenda promoted by the PSG/ PSW in their respective campuses. Even in some of the Islamic university, menganggab that the PSG / PSW is only a collection of the women (read: wife) against men (read: husband). Although the reality is not as extreme in the STAIN Pekalongan, but in this study the authors wanted to see, rather than despite not prove but at least read the truth of the conclusion of the friends network. The author did not conduct in-depth research with a particular approach to scientific method, but the writer is trying to read the reality of everyday experience of the author as part of the academic community in the STAIN Pekalongan. This study is intended as a preliminary description in order to be a reference for the development of ideas STAIN Pekalongan and also be a reference for researchers who want to conduct in-depth research or create a baseline study on gender sensitivity in STAIN Pekalongan toward campus of Rahmatan Lilâ€™Alamin. Abstrak : PenelitianÂ ini berpinjak dari realitas masalah yang telah menjadi subyek pembicaraan di forum jaringan PSG / PSW di seluruh Indonesia, baik PTAIN / S dan Perguruan Tinggi Umum, mengenai kondisi kurangnya respon terhadap agenda pejabat kampus dipromosikan oleh PSG / PSW di kampus masing-masing. Bahkan di beberapa universitas Islam, menganggap bahwa PSG / PSW hanya koleksi wanita (baca: istri) terhadap laki-laki (baca: suami). Meskipun kenyataannya tidak seekstrim di STAIN Pekalongan, tetapi dalam penelitian ini penulis ingin melihat, daripada meskipun tidak membuktikan tapi setidaknya membaca kebenaran kesimpulan dari jaringan teman-teman. Penulis tidak melakukan penelitian mendalam dengan pendekatan tertentu untuk metode ilmiah, tetapi penulis mencoba untuk membaca realitas pengalaman sehari-hari penulis sebagai bagian dari civitas akademika STAIN Pekalongan. Penelitian ini dimaksudkan sebagai gambaran awal untuk menjadi acuan bagi pengembangan ide-ide STAIN Pekalongan dan juga menjadi acuan bagi para peneliti yang ingin melakukan penelitian mendalam atau membuat studi baseline pada sensitivitas gender dalam STAIN Pekalongan menuju kampus rahmatan lil'alamin.